Vergil in Russia : national identity and classical reception - Torlone, Zara Martirosova (Classical presences, 2015)
This volume looks to uncover the nature of Russian reception of Vergil, and argues that the best way to analyze his presence in Russian letters is to view it in the context of the formation and development of Russian national and literary identity